Utilização de ensaios tecnológicos como auxílio na interpretação do polimento de rochas ornamentais - Camargo, Jefferson Luiz [UNESP]; Artur, Antonio Carlos [UNESP]; da Silveira, Leonardo Luiz Lyrio (My University, 2015)
The polishment is the main type of finishing performed in slabs and tiles of rocks, which is done by the friction generated in the rotational motion of abrasive elements disposed in polishing heads, under pressure, against the rock surface. The rock is an active element in the process, therefore the knowledge of its properties, can contribute to improving the understanding of this important stage of processing. Three petrographic types of rocks with distinct textural and structural, were selected for this study, in order to compare the results of characterization tests and try to relate intrinsic characteristics which most influenced the action of wear, supporting information for interpretation of the polishing process. The chosen materials were charnockite, monzogranite and gneiss, known commercially Verde Labrador, Cinza Castelo and Preto Indiano. Among the mechanical-physical tests, the results of the uniaxial compression strength, density, water absorption, coefficient of linear thermal expansion and propagation of longitudinal waves show no direct correlation with experimental results of polishing. On the other hand, the porosity, wear resistance and knoop hardness show apparent direct correlation with the rock polishing.
Use of technological tests as an aid in the interpretation of the dimension stone polishing